Analisa Perilaku Altruisme Dengan Bystander Effect Dan Konformitas Teman Sebaya Mahasiswa Universitas Bina Darma - Mawardah, Mutia; Razzak, Dirga (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2024)
This study aims to determine the relationship between the Bystander-effect and peer conformity with altruistic behavior in students at Bina Darma University in Palembang. The hypothesis proposed in this study is the major hypothesis which states that there is a relationship between bystander-effect and peer conformity with altruism behavior in students of Bina Darma University of Palembang and the first minor hypothesis is the relationship between bystander-effect and altruism behavior in information system students Of Bina Darma University and the second minor hypothesis There is a relationship between peer conformity and altruistic behavior in students of Bina Darma University in Palembang. The method used is quantitative methods. In this study were 389 students of Bina Darma University Palembang. Data collection techniques were carried out using purposive sampling techniques and data collection methods using altruism behavior scale, bystander-effect scale, and peer conformity scale. This research analysis technique uses multiple regression analysis. The results of the research analysis showed a major hypothesis with a value of F = 80.944, a value of R2 = 0.475, and a value (p) = 0.000 (p <0.05), the first minor hypothesis Pearson correlation value is -0.680, value (p) = 0.000 ( p <0.05), and for the second minor hypothesis Pearson correlation is -0.223, the value (p) = 0.01 (p <0.05).